2019
DOI: 10.1021/acs.jchemed.8b00897
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry Game: Creating and Playing a Fun Board Game To Engage Students in Reviewing Stereochemistry Concepts

Abstract: A bilingual (English and Portuguese) innovative teaching method, Stereochemistry Game, is presented in the form of a board/card game to help students in their studies of stereochemistry. Four decks of cards (280 cards in total) and one board have been developed for second-year organic chemistry students in an effort to have them work together to solve stereochemistry problems in the context of a fun board game and to provide an efficient alternative to traditional methods of learning. This game encourages inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 34 publications
0
51
0
Order By: Relevance
“…The design of specific study materials for distant students has been revealed as a key factor for the success of such a model. Many educators have worked on developing innovative specific tools in the past decade, such as the use of videos, , the web, the creation of real-time experiments, or the development of online games with serious educational objectives. The latest technological developments, such as Virtual Reality (VR) , or Augmented Reality (AR) have emerged as interactive, promising, and engaging tools for chemical education that are adaptable for distance learning.…”
Section: Introductionmentioning
confidence: 99%
“…The design of specific study materials for distant students has been revealed as a key factor for the success of such a model. Many educators have worked on developing innovative specific tools in the past decade, such as the use of videos, , the web, the creation of real-time experiments, or the development of online games with serious educational objectives. The latest technological developments, such as Virtual Reality (VR) , or Augmented Reality (AR) have emerged as interactive, promising, and engaging tools for chemical education that are adaptable for distance learning.…”
Section: Introductionmentioning
confidence: 99%
“…Educators have developed educational games [2][3][4][5] to involve students in interactive and entertaining activities 6 . Games are an excellent method of active learning in a recreative environment 7 and many methods have been tested in the past decade 8 : word game 9 , quiz games [10][11][12][13][14][15][16][17][18] , card games 19,20 , dice games 21,22 , board games [23][24][25][26][27] , computer games [28][29][30] and memory/concentration game [31][32][33] . Surprisingly, the use of videogames to illustrate chemical engineering is relatively unexplored in the literature even though pedagogical videogames exist [34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that students have difficulties in 3D visualization, but the good news is that it can be trained. Educators have gone the extra mile to help students overcome the perils of stereochemistry by developing different teaching strategies, including educational games . In the classroom, in order to help the students visualize and conceptualize stereochemistry principles, educators usually use molecular models, such as ball-and-stick .…”
Section: Engaging Students In Learning Activitiesmentioning
confidence: 99%